Applications of titanium dioxide photocatalysis to construction materials state-of-the-art report of the RILEM technical committee 194-TDP - Ohama, Yoshihiko; Gemert, Dionys van 1948- (RILEM State of the Art Reports, 2011)
Titanium dioxide photocatalysis is based on the semiconducting nature of its anatase crystal type. Construction materials with titanium photocatalyst show performances of air purification, self-cleaning, water purification, antibacterial action.This book describes principles of titanium dioxide photocatalysis, its applications to cementitious and noncementitious materials, as well as an overview of standardization of testing methods.